2012
DOI: 10.1111/j.1439-0531.2011.01982.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C Enhances the In vitro Development of Porcine Pre‐implantation Embryos by Reducing Oxidative Stress

Abstract: Vitamin C (Vc) is a natural compound supplemented to culture media to guarantee the appropriate reactive oxygen species (ROS) level, as well as protect cells from oxidative damage and apoptosis. The current study was conducted to determine the effects of Vc (0, 2.5, 5, 10, 20 and 40 μg/ml) on the ROS production, developmental ability and quality of in vitro produced porcine parthenotes. The results show that: (i) the ROS levels in the embryos significantly decrease in the Vc-treated groups compared with the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 21 publications
(45 reference statements)
5
37
0
3
Order By: Relevance
“…10 Vitamin C is also an important cofactor in several enzymatic reactions such as histone demethylases and prolylhydroxylases. 11 Recent studies have demonstrated that vitamin C supplementation produces important effects on stem cell generation, proliferation and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…10 Vitamin C is also an important cofactor in several enzymatic reactions such as histone demethylases and prolylhydroxylases. 11 Recent studies have demonstrated that vitamin C supplementation produces important effects on stem cell generation, proliferation and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, VitC is a well-known antioxidant and it has been reported that embryos exposed to VitC show reduced levels of reactive oxygen species (Wang et al 2002, Hu et al 2012, Li et al 2014) and increased reduced glutathione content (Wongsrikeao et al 2007, Zhang et al 2010, Mallol et al 2015, which lead to lower levels of apoptosis (Jeong et al 2006, Hu et al 2012, Li et al 2014, parameters which have been related to reduced speed of embryo development (Favetta et al 2004, Wale & Gardner 2010. Thus, the antioxidant effect of VitC could reduce DNA damage and checkpoint arrest, accelerating cell cycle progression in SCNT embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (2014) showed that supplementing culture with the proper concentration of vitamin C can protect cells against the damaging effects of ROS by suppressing ROS production and promote stem cell proliferation, regulating the expression of apoptosis-related genes. In fact, vitamin C inhibits pro-apoptotic signals and activates anti-apoptotic signals in vitro (Hu et al, 2012). On the other hand, vitamin E, which is known as a natural antioxidant, reacts with soluble free radicals in lipid membranes and prevents the process of lipid peroxidation by scavenging reactive oxygen species before they can cause damage to the cells (Moreira et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This reduction in the survival rate of SSCs may be caused by the accumulation of toxic products of metabolism and ROS formation (Aliakbari et al, 2017). High levels of ROS production can increase the expression level of ROS-related genes such as bax and the proportion of the pro-apoptotic to anti-apoptotic genes markedly determines cell fate (Hu et al, 2012). In cells that are subject to apoptosis, bax, as a pro-apoptotic protein, forms pores on the mitochondrial membrane and expels cytochrome C from mitochondria to trigger the formation of a large protein complex called apoptosome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation